You Can Help Your Country : English children's work during the Second World War - Mayall, Berry; Morrow, Virginia (Book collections on Project MUSE., 2020)
First published in 2011, You Can Help Your Country: English children's work during the Second World War reveals the remarkable, hidden history of children as social agents who actively participated in a national effort during a period of crisis. In praise of the book, Hugh Cunningham, celebrated author of The Invention of Childhood, wrote: 'Think of children and the Second World War, and evacuation comes immediately to mind. Berry Mayall and Virginia Morrow have a different story to tell, one in which all the children of the nation were encouraged to contribute to the war effort. Many responded enthusiastically. Evidence from school magazines and oral testimony shows children digging for victory, working on farms, knitting comforts for the troops, collecting waste for recycling, running households. What lessons, the authors ask, does this wartime participation by children have for our own time? The answers are challenging.'